Zygophylax kakaiba, a new species of hydroid (Cnidaria: Hydrozoa: Zygophylacidae) from the Philippine Islands - Campos, Felipe Ferreira; Marques, Antonio Carlos; Puce, Stefania; Pérez, Carlos Daniel (Zootaxa, 2016)
The genus Zygophylax Quelch, 1885 includes ca. 50 valid species of leptothecate hydroids that occur mainly in deep waters. Herein we describe Zygophylax kakaiba, sp. nov., collected in the Philippines at a depth of 580 m during the Siboga Expedition. Compared to its congeners, this species is distinguished by the abrupt curvature of the distal third of its hydrothecae towards the adcauline side.